Elucidation of the elusive structure and formula of the active pharmaceutical ingredient bismuth subgallate by continuous rotation electron diffraction. Issue 52 (14th June 2017) - Wang, Yunchen; Takki, Sofia; Cheung, Ocean; Xu, Hongyi; Wan, Wei; Öhrström, Lars; Inge, A. Ken
Abstract : Bismuth subgallate was revealed as a coordination polymer providing insight into its solubility and gas sorption properties. Abstract : Bismuth subgallate has been used in wound and gastrointestinal therapy for over a century. The combination of continuous rotation electron diffraction and sample cooling finally revealed its structure as a coordination polymer. The structure provides insight regarding its formula, poor solubility, acid resistance and previously unreported gas sorption properties.